2000
DOI: 10.13031/2013.2976
|View full text |Cite
|
Sign up to set email alerts
|

Using Soil Attributes and Gis for Interpretation of Spatial Variability in Yield

Abstract: Precision farming application requires better understanding of variability in yield patterns in order to determine the cause-effect relationships. This field study was conducted to investigate the relationship between soil attributes and corn (Zea mays L.)-soybean (Glycine max L.) yield variability using four years yield data from a 22-ha field located in central Iowa. Corn was grown in this field during 1995, 1996, and 1998, and soybean was grown in 1997. Yield data were collected on nine east-west transect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 29 publications
(20 reference statements)
1
41
0
Order By: Relevance
“…Crop yield variability within a field may be due to intrinsic factors such as soil type, soil moisture, and nutrient potential as well as the extrinsic factors such as climate and management practices (Lamb et al, 1997;Bakhsh et al, 2000). Climatic variables are the most dominating factors that also cause temporal variability of crop yields within a field from year to year.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crop yield variability within a field may be due to intrinsic factors such as soil type, soil moisture, and nutrient potential as well as the extrinsic factors such as climate and management practices (Lamb et al, 1997;Bakhsh et al, 2000). Climatic variables are the most dominating factors that also cause temporal variability of crop yields within a field from year to year.…”
Section: Introductionmentioning
confidence: 99%
“…GIS is a powerful tool for determining the integrated effects of the various soil and landscape data layers with crop yield patterns (Bakhsh et al, 2000). The effects of soil and topographic attributes on yield variation can be perceived better when data layers of these attributes are overlaid (Silva and Alexandre, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What information do we need to make an appropriate decision? Bakhsh et al [3] used a statistical approach to characterize the spatio-temporal variability within a field. They found that overall, yield variability was not stable spatially or temporally.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show a correlation between grain yield and soil physical characteristics (SWAN et al, 1987;BAKHSH et al, 2000).…”
Section: Introductionmentioning
confidence: 99%